Building related illness : a procedure to detect symptomatic buildings : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Philosophy in the Department of Agricultural Engineering at Massey University - Sisk, William Edward (Massey University, 1994)
This study examines the topic of building related or building supported illness in the context of a commercial office setting. Numerous reports from the United Kingdom, Scandinavia, Holland, Denmark, Canada and the United States of America, indicate that workers in some office buildings suffer a degree of discomfort and physical symptoms related to building occupancy. The problem is examined in the context of a commercial office environment and the term 'Building Related Illness' (BRI) and it's sub-set 'the Sick Building Syndrome' (SBS) are defined. The illnesses or specific syndromes known to be associated with building related illness are identified. There is ongoing debate as to the valid inclusion of some viral diseases. This study takes a symptomatic approach to the identification of the various syndromes of interest. The numerous elements or stressors known to cause particular symptoms are identified and discussed. BRI is identified by an unusual or extraordinary frequency of certain physical symptoms being experienced by the occupancy of a particular building. However, the symptoms of interest are found in the general community at an unknown incidence rate. The exact role a building and it's association with a symptom or cluster of symptoms is, more often than not, difficult to ascertain. There are a number of confounding elements which need to be considered and eliminated before the building itself can be implicated as a causal factor. This is because the general nature of the symptoms associated with BRI can be caused by other factors. Broadly, the other causative factors may be 'Job Related' or 'Ergonomically Related' (eg. poorly designed work stations). It is well documented that workers in menial or less interesting employment report a higher prevalence of BRI type symptoms. The role of chronic diseases in relation to commercial buildings are discussed and the alternative paradigm to dealing with these stressors is examined. Finally, a statistical method for identifying a 'problem building' is piloted on two dissimilar buildings and the results are analyzed. The prevalence of symptom reporting amongst certain cohorts is similar to a number of overseas studies. It was concluded that the proposed model was successful in identifying symptom clusters amongst certain cohorts within the buildings surveyed. In this respect the piloted questionnaire was successful. The questionnaire is critically reviewed and a number of amendments are suggested.
Keywords: Sick building syndrome; Environmental engineering; Health; Buildings